1995
DOI: 10.1085/jgp.106.3.525
|View full text |Cite
|
Sign up to set email alerts
|

Regulatory volume decrease in cultured kidney cells (A6): role of amino acids.

Abstract: Volume regulation was studied in A6 epithelia grown on permeable supports by measuring cell thickness (To) while simultaneously recording short circuit current (Ix) and tmalsepithelial conductance (Gt). Lowering the tonicity of the basolateral solution (Wb) from 250 or 215 to 140 mOsm/kg elicited a rapid rise in Tc followed by a regulation of the cell volume towards control. This decrease in Tc displays the characteristics of the regulatory volume decrease (RVD). Upon restoring the isoosmotic conditions, T~ de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
17
0

Year Published

1995
1995
2012
2012

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 28 publications
3
17
0
Order By: Relevance
“…Indeed, the %To l~ec value expected for an ideal osmometer is 54% whereas the experimental values ranged from 55% to 61%. As the Tc u~ values were only recorded 20 min after the solution change in period III, the almost ideal osmotic behaviour of the cells confirms the absence of a post-RVD RVI, as described in a previous paper [7]. Further insight into the nature of the mechanism responsible for CI-excretion could be obtained by the use of C1 -channel blockers.…”
Section: 'O 40supporting
confidence: 81%
See 3 more Smart Citations
“…Indeed, the %To l~ec value expected for an ideal osmometer is 54% whereas the experimental values ranged from 55% to 61%. As the Tc u~ values were only recorded 20 min after the solution change in period III, the almost ideal osmotic behaviour of the cells confirms the absence of a post-RVD RVI, as described in a previous paper [7]. Further insight into the nature of the mechanism responsible for CI-excretion could be obtained by the use of C1 -channel blockers.…”
Section: 'O 40supporting
confidence: 81%
“…In several cell types it has been demonstrated that the RVD is mainly mediated by amino acid and/or KC1 excretion [24]. Our previous study [7] focused on the role of amino acids in the development of the RVD and demonstrated an effect of these compounds which could not fully account for the RVD. In this paper, we test the involvement of K + and C1-.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Crypt epithelial volume and epithelial cell height measured on optical cross sections were used as an index of cell volume, as previously described for polarized epithelium (16,20,61). Enteroids from sex-matched, littermate WT and Cftr KO mouse pairs were grown on glass chamber slides.…”
Section: Methodsmentioning
confidence: 99%